Asymmetric photoredox transition-metal catalysis activated by visible light - Huo, Haohua; Shen, Xiaodong; Wang, Chuanyong; Zhang, Lilu; Röse, Philipp; Chen, Liang-An; Harms, Klaus; Marsch, Michael; Hilt, Gerhard; Meggers, Eric (Nature (London), 2014)
A chiral iridium complex serves as a sensitizer for photoredox catalysis and at the same time provides very effective asymmetric induction for the enantioselective alkylation of 2-acyl imidazoles; the metal centre simultaneously serves as the exclusive source of chirality, the catalytically active Lewis acid centre, and the photoredox centre. A new asymmetric photocatalyst The growing demand for optically active compounds in the chemical and pharmaceutical industries is focusing attention on asymmetric photocatalysis as a potentially economical means of synthesis, combining visible light photoredox chemistry with asymmetric catalysis. In this manuscript, the authors show that a chiral iridium complex can serve as a sensitizer for photoredox catalysis and at the same time provide effective asymmetric induction for the enantioselective alkylation of 2-acyl imidazoles. This new asymmetric photoredox catalyst, in which the metal centre serves simultaneously as the exclusive source of chirality, the catalytically active Lewis acid centre, and the photoredox centre, offers new opportunities for the 'green' synthesis of non-racemic chiral molecules. Asymmetric catalysis is seen as one of the most economical strategies to satisfy the growing demand for enantiomerically pure small molecules in the fine chemical and pharmaceutical industries 1 . And visible light has been recognized as an environmentally friendly and sustainable form of energy for triggering chemical transformations and catalytic chemical processes 2 , 3 , 4 , 5 . For these reasons, visible-light-driven catalytic asymmetric chemistry is a subject of enormous current interest 2 , 3 , 4 , 5 . Photoredox catalysis provides the opportunity to generate highly reactive radical ion intermediates with often unusual or unconventional reactivities under surprisingly mild reaction conditions 6 . In such systems, photoactivated sensitizers initiate a single electron transfer from (or to) a closed-shell organic molecule to produce radical cations or radical anions whose reactivities are then exploited for interesting or unusual chemical transformations. However, the high reactivity of photoexcited substrates, intermediate radical ions or radicals, and the low activation barriers for follow-up reactions provide significant hurdles for the development of efficient catalytic photochemical processes that work under stereochemical control and provide chiral molecules in an asymmetric fashion 7 . Here we report a highly efficient asymmetric catalyst that uses visible light for the necessary molecular activation, thereby combining asymmetric catalysis and photocatalysis. We show that a chiral iridium complex can serve as a sensitizer for photoredox catalysis and at the same time provide very effective asymmetric induction for the enantioselective alkylation of 2-acyl imidazoles. This new asymmetric photoredox catalyst, in which the metal centre simultaneously serves as the exclusive source of chirality, the catalytically active Lewis acid centre, and the photoredox centre, offers new opportunities for the ‘green’ synthesis of non-racemic chiral molecules.